2006
DOI: 10.1016/j.jinf.2006.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a strain of community-associated methicillin-resistant Staphylococcus aureus widely disseminated in the United States

Abstract: A highly stable strain of Staphylococcus aureus with a pulsed-field gel electrophoresis type of USA300 and multilocus sequence type 8 has been isolated from patients residing in diverse geographic regions of the United States. This strain, designated USA300-0114, is a major cause of skin and soft tissue infections among persons in community settings, including day care centers and correctional facilities, and among sports teams, Native Americans, men who have sex with men, and military recruits. The organism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
221
3
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(249 citation statements)
references
References 59 publications
(29 reference statements)
17
221
3
8
Order By: Relevance
“…The most prevalent CA-MRSA clones in the United States have the USA300 pulsotype harboring staphylococcal cassette chromosome mec (SCCmec) IV and PantonValentine leukocidin (42,43). The community-based epidemic of MRSA led us to think that that MRSA became as prevalent as penicillin-resistant S. aureus strains in the community, as suggested previously by Chambers (6).…”
mentioning
confidence: 85%
“…The most prevalent CA-MRSA clones in the United States have the USA300 pulsotype harboring staphylococcal cassette chromosome mec (SCCmec) IV and PantonValentine leukocidin (42,43). The community-based epidemic of MRSA led us to think that that MRSA became as prevalent as penicillin-resistant S. aureus strains in the community, as suggested previously by Chambers (6).…”
mentioning
confidence: 85%
“…USA300 isolates typically are resistant only to beta-lactam and macrolide antimicrobial agents and contain genes for the PVL toxin, which typically are not present in strains of healthcare-associated MRSA. 23 Recent studies of acute pneumonia with animal models and in humans have suggested that the PVL toxin-alone or in combination with other virulence factors-is associated with the development of necrotizing pneumonia. [24][25][26][27][28][29][30] In our study, 23 patients with MRSA CAP had strains that contained PVL toxin, and these patients had longer stays in hospital and higher total hospital charges than those with MRSA CAP not containing the PVL toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Reference strains were obtained from the American Type Culture Collection and included methicillin-susceptible and meth-icillin-resistant S. aureus strains, as well as coagulase-negative staphylococcal species (Table 1). Additional reference strains representing wellcharacterized U.S. strains of MRSA described by Tenover and Goering (13,14) were obtained from Ashley Robinson. The MRSA strains employed in this study represented five staphylococcal cassette chromosome mec element (SCCmec) types and subtypes (I, II, III, IV, and IVa).…”
Section: Methodsmentioning
confidence: 99%